Velocity and accuracy as performance criteria for three different soccer kicking techniques - Sterzing, T.; Lange, J. S.; Wächtler, T.; Müller, C.; Milani, T. L. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Kicking velocity (KV) and kicking accuracy (KA) of 19 experienced male soccer players were examined for the full instep, the inner instep, and the side foot kick. Measurements were performed simultaneously by a radar gun (KV) and a newly introduced high-speed-video camera set-up (KA). Subjects had two different tasks: to kick as fast as possible (Max KV) and to kick as accurate as possible (Max KA) with each kicking technique. Six repetitive kicks were performed for each required condition. The full instep and the inner instep kick were faster compared to the side foot kick for both performance tasks. In contrast, the side foot kick was the more accurate technique compared to the inner instep and the full instep kick, also for both performance tasks. Kicking variability between and within subjects was generally low for KV and generally high for KA for all kicking. It is concluded that velocity control is easier to achieve than accuracy control for soccer kicks.